2020
DOI: 10.1371/journal.pntd.0008705
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of invasive Aedes mosquitoes along Swiss traffic axes reveals different dispersal modes for Aedes albopictus and Ae. japonicus

Abstract: Over the past three decades, Europe has witnessed an increased spread of invasive aedine mosquito species, most notably Aedes albopictus, a key vector of chikungunya, dengue and Zika virus. While its distribution in southern Europe is well documented, its dispersal modes across the Alps remain poorly investigated, preventing a projection of future scenarios beyond its current range in order to target mosquito control. To monitor the presence and frequency of invasive Aedes mosquitoes across and beyond the Alps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…In Switzerland, results from an ovitrap network also show great dispersal capacities for Ae. japonicus between 2013 and 2018, and as suggested by the authors, these results favor an active dispersal ( Müller et al 2020 ). At the individual level, it was reported that Ae.…”
Section: Discussionsupporting
confidence: 60%
“…In Switzerland, results from an ovitrap network also show great dispersal capacities for Ae. japonicus between 2013 and 2018, and as suggested by the authors, these results favor an active dispersal ( Müller et al 2020 ). At the individual level, it was reported that Ae.…”
Section: Discussionsupporting
confidence: 60%
“…Most recently, the 2016 Zika virus (ZIKV) epidemic swept through South and Central America wreaking havoc on scores of unborn children by causing microcephaly in utero ( Hills et al., 2017 ; Lee and Ng, 2018 ). In addition to these outbreaks, Aedes albopictus , a vector for ZIKV and dengue virus (DENV) has been found consistently in recent years in central Europe ( Müller et al., 2020 ), and the prevalence of tick-borne diseases is at a record high. These alarming trends correlate with warming temperatures due to climate change, which expand the range of mosquitoes and ticks ( Brady and Hay, 2020 ; Brugueras et al., 2020 ; Dobler, 2010 ; McPherson et al., 2017 ; Medlock et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…From southern Europe, where it has become rapidly established, adults have been passively transported further north in cars and trucks (Eritja et al., 2017; Scholte & Schaffner, 2007). In Germany and Switzerland, this mosquito species has been found in particular along freeway routes from southern Europe (Becker et al., 2013; Flacio et al., 2016; Müller et al., 2020).…”
Section: Introductionmentioning
confidence: 99%